CREATING A GOOD ATMOSPHERE FOR SPEAKING ACTIVITY IN THE CLASSROOM - Frederykus Ege; Yokie Prasetya Dharma (STKIP Persada Khatulistiwa Sintang, 2018)
The purpose of this article is to share to other teachers about an activity that my students have enjoyed. The objective of this article is to allow the students to practice their oral skills and express their idea in an interesting topic. Even the activity is not something new but with appropriate approach, this activity can run well and give new atmosphere in your classroom activity. This activity has applied for the tenth year of IPA of senior High School students in a private school in Sintang regency. Besides from the activity, they enjoyed the activities with group work discussion as they could learn from their friends and supported by the teacher. No student sits in their seat without involving in the activity. It can be concluded that role-play learning provides opportunities for students to use and apply their subject knowledge and skill to deepen understanding. It can be seen that the study of Role-play also can improve the students’ score in speaking skill test.Keywords: Good Atmosphere, Speaking